The role of internship participation and conscientiousness in developing career adaptability: A five-wave growth mixture model analysis - Ocampo, Anna Carmella G. (Animo Repository, 2020)
Career adaptability has been conceptually and empirically linked with successful career transitions. However, research on the antecedents of career adaptability dimensions (i.e., concern, control, curiosity, and confidence) among students in school-to-work transition contexts remains sparse. In this paper, we investigate whether internship participation develops career adaptability over time and whether interns' conscientiousness supports faster development of career adaptability. Data were obtained from 173 undergraduate hotel and restaurant management students in China across five measurement periods. Growth mixture modeling analyses revealed that all career adaptability dimensions increased linearly over time after internship participation. In contrast, there was no growth in career adaptability except for the concern dimension among those who did not participate in internship. Interns' conscientiousness did not increase the rates in which career adaptability develops. The ancillary results of the study, however, showed that pre-internship levels of career adaptability dimensions influence their eventual development. Overall, our findings offer theoretical and practical implications for vocational scholars and career counsellors in supporting and sustaining students' career adaptability development. © 2020